Protective effect of basic fibroblast growth factor-heparin and neurotoxic effect of platelet factor 4 on ischemic neuronal loss and learning disability in gerbils - Wen, T.-C.; Matsuda, S.; Yoshimura, H.; Aburaya, J.; Kushihata, F.; Sakanaka, M. (NEUROSCIENCE, 1995)
Platelet factor 4, which has a potent affinity for heparin, has been shown to inhibit the binding of basic fibroblast growth factor to the cell surface receptor and to counteract the biological activities of basic fibroblast growth factor in certain peripheral tissues. In the present in vitro [ 125I]basic fibroblast growth factor binding experiments, platelet factor 4 consistently inhibited the binding of iodinated basic fibroblast growth factor to cell membranes of the gerbil hippocampus. To investigate the in vivo function of endogenous basic fibroblast growth factor and/or basic fibroblast growth factor receptor possibly activated in the ischemic gerbil brain, we infused platelet factor 4 continuously into the left lateral ventricle with an osmotic minipump. When platelet factor 4 infusion was started within three days after a 3-min ischemic insult, it significantly enhanced ischemia-induced learning disability and ischemic neuronal loss in the CA1 region of the hippocampus, as demonstrated by the results of the step-down passive avoidance task and by subsequent histological examinations. Infusion of platelet factor 4 into the cerebral ventricle of intact gerbils did not affect learning ability or CA1 neuron number. Basic fibroblast growth factor-neutralizing antibody, when infused continuously in the cerebral ventricle, also exhibited a neurotoxic effect in ischemic but not intact gerbils. Basic fibroblast growth factor co-infused with heparin, but not basic fibroblast growth factor alone, rescued a significant number of ischemic neurons which were destined to degenerate without the infusion of heparinized basic fibroblast growth factor, and it prevented ischemia-induced learning disability. Basic fibroblast growth factor infusion prior to platelet factor 4 treatment abolished almost completely the neurotoxic effect of platelet factor 4 on the ischemic hippocampal CA1 region. These findings suggest that (1) platelet factor 4 as a putative basic fibroblast growth factor receptor antagonist exerts a neurotoxic effect on the ischemic hippocampus and so does basic fibroblast growth factor-neutralizing antibody; (2) heparin is indispensible for basic fibroblast growth factor to retain neurotrophic activity; (3) basic fibroblast growth factor infused before platelet factor 4 treatment occupies the binding sites of basic fibroblast growth factor on the cell surfaces of ischemic neurons; and (4) the later infusion of platelet factor 4, even though it blocks, partially, the subsequent binding of basic fibroblast growth factor to the receptor, can no longer suppress the basic fibroblast growth factor-mediated intracellular signal transduction in favor of neuronal survival. Thus, the present study indicates a pivotal role of endogenous basic fibroblast growth factor in the survival and functional recovery of ischemic neurons. The transient neurotoxic effect of platelet factor 4 after brain ischemia and the molecular basis of interaction between platelet factor 4, basic fibroblast growth factor and heparin are discussed.